U–Pb zircon geochronology, Sr–Nd geochemistry, petrogenesis and tectonic setting of Mahoor granitoid rocks (Lut Block, Eastern Iran). (1st November 2015) - Beydokhti, Roohollah Miri; Karimpour, Mohammad Hassan; Mazaheri, Seyed Ahmad; Santos, José Francisco; Klötzli, Urs
Highlights: The Mahoor granitoid rocks were formed in the early Oligocene (31.9 ± 0.2 Ma). Mahoor granitoid rocks formed in a subduction regime. These granitoid rocks are I-type granites. The Mahoor granitoid rocks were generated by magma mixing between mantle and crustal-derived melts. Abstract: The Mahoor Cu–Zn-bearing porphyritic granitoid rocks belong to the Lut Block volcanic–plutonic belt (central Eastern Iran). These granitoid rocks occur mainly as dykes and stocks that intrude into Eocene volcanics and pyroclastic rocks. Petrographically, all the studied intrusives display porphyritic textures with mm-sized phenocrysts, most commonly of plagioclase and hornblende, embedded in a fine-grained groundmass with variable amounts of plagioclase, hornblende, clinopyroxene, quartz and opaque minerals. Hydrothermal alteration affected these granitoid rocks, as revealed by the common occurrence of sericite, chlorite, titanite, epidote and calcite. Chemical classification criteria show that the intrusives may be named as gabbrodiorites, diorites, monzodiorites and tonalites. Major elements geochemistry reveals that all the studied lithologies are typically metaluminous (A/CNK ⩽ 0.9). Magnetic susceptibility (1485 × 10 −5 SI) together with mineralogical and geochemical features shows that they belong to magnetite granitoid series (I-type). Trace element patterns normalized to chondrite and primitive mantle are very similar to each other and show enrichments in LREE relative to HREE and in LILE relative to HFSE, as well as negative anomalies of Ta, Nb and Ti. Eu/Eu ∗ ratios vary from 0.88 (in the most mafic composition) to 0.65, showing that plagioclase played a role in magma differentiation. LA-MC-ICP-MS U–Pb zircon data from a diorite, yielded similar concordia ages of ca. 31.88 ± 0.2 Ma (Error: 2 σ ), which corresponds to the Oligocene period. These granitoid rocks have ( 87 Sr/ 86 Sr) i values vary between 0.7055 and 0.7063. In terms of isotopic compositions, while εNdi is between −0.6 and −2.5, suggesting that magmas underwent contamination through being exposed to the continental crust. The whole set of geochemical data agree with the emplacement of the studied intrusions in a magmatic belt above a subduction zone. Primitive magmas should have formed by melting of mantle wedge peridotite, and during magma ascent to crustal levels, both magma differentiations took place by crystal fractionation and crustal contamination. Sulfide mineralizations (pyrite, chalcopyrite and sphalerite) related to these granitoid rocks is common and occurs as both disseminated and hydrothermal veins, indicating a high mineralization potential for this area.